Efforts to Improve English Speaking Ability of Five to Six-Years-Old Bilingual School Students Through Hand Puppet Media - Fitria, Nila; Farastiwi, Atria (Universitas Islam Negeri Raden Intan Lampung, 2021)
This classroom action research was motivated by the five to six-year-old students’ low English speaking ability in bilingual schools, especially in pronouncing, adding vocabulary, and forming sentences. This research aims to improve the English language skills of five to six-year-old students using hand puppets. This research was conducted from April 9 to May 4, 2018, at the TK IT Al Ikhlas Islamic Bilingual School by employing Kemmis's and Mc Taggart’s model in two cycles with three meetings each. The subjects of this research consisted of twelve students (seven males and five females). Based on the research results, there was an increase in English language skills through hand puppet media. In conclusion, the factors affecting students’ English speaking skills are familiar vocabulary, clear and easy to imitate teacher's pronunciation, exciting and varied media, and opportunities for them to use hand puppets while imitating the teacher. The researchers concluded that the hand puppet media could improve the five to six-year-old students' language skills.